2003
DOI: 10.1001/archinte.163.20.2460
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Cardiovascular Risk Profile in Middle Age and Health-Related Quality of Life in Older Age

Abstract: Favorable cardiovascular risk profile in middle age is associated with better quality of life and lower risk of diseases in older age. Moreover, the fewer the risk factors, the higher the quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 44 publications
7
86
0
1
Order By: Relevance
“…The United States is advantaged in that CVD risk factor improvements and heart and stroke mortality declines continued despite increases in BMI (37, 38). Daviglus et al (16) showed that improved CVD risk factor profiles in middle age were related to improved quality of life in elderly persons. Other recent analyses found that the obesity-related metabolic syndrome was not strongly predictive of CVD risks and renal dysfunction, suggesting that current BMI may not be the best predictor of health effects but instead perhaps whether BMI was raised earlier in life and stayed raised for a long (several decades) period of time (4).…”
Section: Cvd and Diabetesmentioning
confidence: 99%
“…The United States is advantaged in that CVD risk factor improvements and heart and stroke mortality declines continued despite increases in BMI (37, 38). Daviglus et al (16) showed that improved CVD risk factor profiles in middle age were related to improved quality of life in elderly persons. Other recent analyses found that the obesity-related metabolic syndrome was not strongly predictive of CVD risks and renal dysfunction, suggesting that current BMI may not be the best predictor of health effects but instead perhaps whether BMI was raised earlier in life and stayed raised for a long (several decades) period of time (4).…”
Section: Cvd and Diabetesmentioning
confidence: 99%
“…After 26 years of follow-up, quality of life was substantially and progressively lower among participants of the Chicago Heart Association Detection Project in Industry Study with a greater number of CVD risk factors at baseline. 19 A recent study by Liu et al 16 presented a comparison of coronary heart disease event rates and risk factor prevalence in the Chinese Multiprovincial Cohort Study (CMCS) and the Framingham Heart Study. Ten-year coronary heart disease event rates for men and women enrolled in the CMCS were 1.5% and 0.6%, respectively.…”
Section: Circulation August 2 2005mentioning
confidence: 99%
“…1 Large-scale prospective cohort studies of non-Hispanic/ Latino young adult and middle-aged men and women with decades of follow-up have demonstrated multiple beneficial outcomes associated with favorable levels of all major CVD risk factors (ie, low risk [LR]). [2][3][4][5][6][7] LR status in young adulthood or middle age is associated with markedly lower age-specific CVD and total mortality rates, higher life expectancies, lower health care costs, and better quality of life at older ages. [2][3][4][5][6][7] The importance of population-wide LR status to overcome the CVD epidemic is now widely accepted, with LR status forming the basis of the ideal cardiovascular health construct described in the American Heart Association (AHA) 2020 Impact Goal.…”
mentioning
confidence: 99%